Ideological alignment and the distribution of public expenditures. Issue 3 (4th May 2018) - Kleider, Hanna; Röth, Leonce; Garritzmann, Julian L.
Abstract: This article revisits the influential partisan alignment hypothesis, which posits that subnational governments aligned with central governments exhibit higher expenditures. To promote their own and their party's re-election chances, central government politicians allocate more resources to ideologically aligned co-partisans at the subnational level. Consequently, aligned subnational governments exhibit higher expenditures than non-aligned ones. This article examines alignment effects in subnational education spending. Education is a crucial test case because, unlike other expenditures, the allocation of education spending is discretionary and often does not follow precise formulas. Using a novel dataset covering 266 subnational regions in 14 countries over 20 years, we offer the first cross-country analysis of alignment effects. Controlling for rival explanations, the findings reveal alignment effects on subnational education expenditures. Furthermore, political institutions matter, as alignment effects are stronger in countries where subnational governments have more discretion over education policy while lacking their own revenue sources (vertical fiscal imbalance). These findings imply that decentralisation might increase educational and socio-economic inequalities.